Oncolytic Viruses for Cancer Therapy: Barriers and Recent Advances - Zheng, Meijun (Mol Ther Oncolytics, 2019)
Oncolytic viruses (OVs) are powerful new therapeutic agents in cancer therapy. With the first OV (talimogene laherparepvec [T-vec]) obtaining US Food and Drug Administration approval, interest in OVs has been boosted greatly. Nevertheless, despite extensive research, oncolytic virotherapy has shown limited efficacy against solid tumors. Recent advances in viral retargeting, genetic editing, viral delivery platforms, tracking strategies, OV-based gene therapy, and combination strategies have the potential to broaden the applications of oncolytic virotherapy in oncology. In this review, we present several insights into the limitations and challenges of oncolytic virotherapy, describe the strategies mentioned above, provide a summary of recent preclinical and clinical trials in the field of oncolytic virotherapy, and highlight the need to optimize current strategies to improve clinical outcomes.